Implementation of a Nurse-Driven Asthma Pathway in the Pediatric Intensive Care Unit. Issue 6 (15th November 2021) - Flaherty, Michael R.; Whalen, Kimberly; Lee, Ji; Duran, Carlos; Alshareef, Ohood; Yager, Phoebe; Cummings, Brian
Abstract : Background: Asthma is one of the most common conditions requiring admission to a pediatric intensive care unit. Dosing and weaning medications, particularly bronchodilators, are highly variable, and evidence-based weaning algorithms for clinicians are lacking in this setting. Methods: Patients admitted to a quaternary pediatric intensive care unit diagnosed with acute severe asthma were evaluated for time spent receiving continuous albuterol therapy, the length of stay in the intensive unit care unit, and the length of stay in the hospital. We developed an asthma pathway and continuous bronchodilator weaning algorithm to be used by bedside nurses. We then implemented two major Plan-Do-Study-Act cycles to facilitate the use of the pathway. They included implementing the algorithm and then integrating it as a clinical decision support tool in the electronic medical record. We used standard statistics and quality improvement methodology to analyze results. Results: One-hundred twenty-six patients met inclusion criteria during the study period, with 32 during baseline collection, 60 after weaning algorithm development and implementation, and 34 after clinical decision support implementation. Using quality improvement methodology, hours spent receiving continuous albuterol decreased from a mean of 43.6 to 28.6 hours after clinical decision support development. There were no differences in length of stay using standard statistics and QI methodology. Conclusion: Protocolized asthma management in the intensive care unit setting utilizing a multidisciplinary approach and clinical decision support tools for bedside nursing can reduce time spent receiving continuous albuterol and may lead to improved patient outcomes.